The Influence of Product Diversity, Product Quality, and Service Quality on Customer Purchasing Decisions at Mr.DIY Tunjungan Plaza Surabaya - Nafa Shoimah; Siti Ning Farida (Universitas KH. Abdul Chalim Mojokerto, 2025)
As business rapidly develops these days, there is fierce competition among business players, particularly in the retail sector. Mr.DIY is one of the retail businesses competing in the current market by offering a wide variety of products. This research was conducted to investigate the influence of product diversity, product quality, and service quality on customer purchasing decisions at Mr.DIY Tunjungan Plaza Surabaya. The type of research used is quantitative. The population in this study is customers who have purchased Mr.DIY products at Tunjungan Plaza Surabaya, who are at least 17 years old and live in Surabaya. This research employed a sample of 100 respondents using the non-probability and purposive sampling methods. Multiple linear regression analysis was employed to analyze the data, which was tested using SPSS version 27. The findings of this study indicate that product diversity, product quality, and service quality have a simultaneous impact on customer purchasing decisions. Product diversity has a significant influence on purchasing decisions, product quality has a significant influence on purchasing decisions, and service quality has a significant influence on purchasing decisions.